2014
DOI: 10.1007/s40097-014-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

Triethylamine induced synthesis of silver and bimetallic (Ag/Au) nanoparticles in glycerol and their antibacterial study

Abstract: Formation of Ag nanoplates in the presence of glycerol/triethylamine/polyvinylpyrrolidone without using any external reducing agent is shown for the first time. This approach is a unique and size-controlled synthetic method for the preparation of Ag nanoplates. Results reveal that addition of triethylamine to the precursor reaction mixture plays an important role both as a reagent for initiation and accelerator to produce nanoparticles at room temperature in the presence of glycerol. The basicity of the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Then, this solution was transferred into 50 mL cyclohexane in 100 mL flask. Additionally, then, 0.5 mL aqueous solutions of sodium periodate (NaIO 4 ), e.g., 50, 100, and 200 mole% based on TA amount was added in the solution followed by the addition of 10 µL triethylamine (TEA), an accelerator for the reaction by acting as proton acceptor [ 43 , 44 ] and mixed with homogenizer (IKA, T25 digital ULTRA TURRAX) at 5000 rpm at 60 °C for 45 min. After that, the obtained p (TA) particles were precipitated by using a centrifuge (BECKMAN COULTER, Allegra 64R Centrifuge) at 10,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Then, this solution was transferred into 50 mL cyclohexane in 100 mL flask. Additionally, then, 0.5 mL aqueous solutions of sodium periodate (NaIO 4 ), e.g., 50, 100, and 200 mole% based on TA amount was added in the solution followed by the addition of 10 µL triethylamine (TEA), an accelerator for the reaction by acting as proton acceptor [ 43 , 44 ] and mixed with homogenizer (IKA, T25 digital ULTRA TURRAX) at 5000 rpm at 60 °C for 45 min. After that, the obtained p (TA) particles were precipitated by using a centrifuge (BECKMAN COULTER, Allegra 64R Centrifuge) at 10,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that Au@Ag core–shell nanoparticles exhibited enhanced antibacterial activity because of the Ag shell around the Au core. 82 …”
Section: Gold Is Unique and Worthy Of Importancementioning
confidence: 99%
“…Ag, Au and Au@Ag core shell NPs were prepared by dissolving AgNO 3 or HAuCl 4 salt in aqueous solution with (0-40%vol) glycerol with triethylamine as reducing agent in the presence of PVP or SDS (sodium dodecyl sulfate) as stabilizing agents at room temperature. For the bimetallic system, AuNPs were firstly prepared and after AgNO 3 was added with triethylamine and glycerol [54].…”
Section: Metal-based Nanoparticles From Group 11mentioning
confidence: 99%